Preparation of pullulanase/Cu3(PO4)2 hybrid nanoflower and its catalytic performance as an immobilized enzyme - Bilgi, Mesut; Peksel, Aysegul (ELSEVIER, 2025)
A commercially important pullulanase enzyme that hydrolyzes alpha-1,6 glycosidic linkages in pullulan was immobilized as pullulanase/Cu3(PO4)2 hybrid nanoflower. Free and immobilized enzymes both showed the highest activity at 25 degrees C. The optimum pH of the free enzyme was 4.5, and the immobilized enzyme was 5.5. Immobilization provided the enzyme with good thermal and pH stability. Even after 18 weeks, immobilized enzyme stored at 4 or-20 degrees C still have 40 % and 60 % activity, respectively. The reusability of the immobilized enzyme was very good with nearly 75 % activity after 8 cycles. Immobilization provided good protection against Cu2+, which is one of the main inhibitors of the pullulanase.
Keywords: Pullulanase; Hybrid nanoflower; Immobilized enzyme; EXPRESSION; Biochemistry & Molecular Biology; Chemistry; Polymer Science